A Candidate Drug Screen Strategy: The Discovery of Oroxylin A in Scutellariae Radix Against Sepsis via the Correlation Analysis Between Plant Metabolomics and Pharmacodynamics - Han, Lingyu; Yuan, Yue; Chen, Xinyi; Huang, Jian; Wang, Guan; Zhou, Chao; Dong, Jianjian; Zhang, Na; Zhang, Yuxin; Yin, Hang; Jiang, Yunyao (Frontiers in Pharmacology, 2022)
Sepsis is an acute systemic infectious disease with high mortality, which needs more effective treatment. Scutellariae Radix (SR), a commonly used traditional Chinese medicine (TCM) for clearing heat and detoxification, contains rich natural products with anti-inflammatory activity. It was found that the anti-inflammatory activities of SR extracts from different ecological conditions varied wildly in previous studies. Therefore, in this study, a screening strategy of anti-sepsis active components from SR based on plant metabolomics and pharmacodynamic correlation analysis was established, and the mechanism was explored. First of all, a mass spectrum database of SR (above 240 components) was established to lay the foundation for identification of liquid chromatography tandem mass spectrometry (LC-MS/MS) based plant metabolomics. Through the correlation analysis of plant metabolomics and anti-inflammatory activity of SR extracts from different ecology, 10 potential components with high correlation coefficient were preliminarily screened. After screening of anti-inflammatory activity and toxicity at the cellular level, the following pharmacodynamic evaluation in vivo found that Oroxylin A had the potentiality of anti-sepsis both in LPS and CLP induced endotoxemia mice. Network pharmacology and western blot (WB) results indicated that Oroxylin A significantly inhibited toll-like receptor 4/nuclear factor-kappa B (TLR4/NF-κB) signaling pathway, which furtherly confirmed by secreted embryonic alkaline phosphatase (SEAP) assay. Moreover, the molecular docking analysis indicated that Oroxylin A might competitively inhibit LPS binding to myeloid differentiation 2 (MD-2) to block the activation of TLR4. The study provided a feasible research strategy for the screening and discovery of anti-sepsis drugs from TCM which is a natural candidate drug library.